2007
DOI: 10.1073/pnas.0706167104
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglobin attenuates β-amyloid neurotoxicity in vitro and transgenic Alzheimer phenotype in vivo

Abstract: Neuroglobin (Ngb), a vertebrate globin expressed primarily in neurons, is induced by and protects against neuronal hypoxia and cerebral ischemia. To investigate the spectrum and mechanism of Ngb's neuroprotective action, we studied the effect of transgenic overexpression of Ngb on NMDA and ␤-amyloid (A␤) toxicity in murine cortical neuron cultures in vitro and on the phenotype of Alzheimer's disease (AD) transgenic (APP Sw,Ind) mice. Compared with cortical neuron cultures from wild-type mice, cultures from Ngb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 34 publications
2
102
0
Order By: Relevance
“…In fact, it has been demonstrated that experimentally decreased Ngb levels reduced, whereas overexpression of Ngb improved survival of cultured neurons (Liu et al, 2009;Sun et al, 2001) or isolated islet of Langerhans cells (Mendoza et al, 2005). Ngb may also protect neurons from β-amyloid-induced neurotoxicity and thus from Alzheimer's disease (Khan et al, 2007). Mice over-expressing Ngb in the brain showed reduced tissue infarction and improved pathology after ischemia (Khan et al, 2006;Sun et al, 2003;Wang et al, 2008).…”
Section: Neuroprotective Properties Of Neuroglobinmentioning
confidence: 99%
“…In fact, it has been demonstrated that experimentally decreased Ngb levels reduced, whereas overexpression of Ngb improved survival of cultured neurons (Liu et al, 2009;Sun et al, 2001) or isolated islet of Langerhans cells (Mendoza et al, 2005). Ngb may also protect neurons from β-amyloid-induced neurotoxicity and thus from Alzheimer's disease (Khan et al, 2007). Mice over-expressing Ngb in the brain showed reduced tissue infarction and improved pathology after ischemia (Khan et al, 2006;Sun et al, 2003;Wang et al, 2008).…”
Section: Neuroprotective Properties Of Neuroglobinmentioning
confidence: 99%
“…The expression of Ngb in most areas of the brain does not colocalize with neuronal nitric oxide synthase [9] . In Ngb-transgenic mice, the expression of endothelial nitric oxide synthase increases [10] . Therefore, determining whether NO-scavenging is an important physiological function of Ngb in the brain requires further study.…”
Section: Introductionmentioning
confidence: 99%
“…Ngb was shown to play a role in brain recovery from stroke (5) and transgenic mice overexpressing Ngb proved more resilient to experimentally induced cerebral and myocardial ischemia (6). Cultured neuronal cells from transgenic mice overexpressing Ngb showed a decreased beta-amyloid toxicity (7), suggesting a potential inhibiting role of Ngb in the onset of Alzheimer's disease.…”
mentioning
confidence: 99%